2020
DOI: 10.1515/chem-2020-0046
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the effect of khat (Catha edulis) chewing on the pharmacokinetics of the antiplatelet drug clopidogrel in rats using the newly developed LC-MS/MS technique

Abstract: AbstractClopidogrel (CLOP) is widely used worldwide for cardiovascular complications. CLOP is highly metabolized in the liver to its active metabolite by cytochrome P450 enzymes. Studies have shown that khat, an addictive substance, is a powerful inhibitor of cytochrome P450 enzymes and can influence the metabolism of drugs that are concomitantly used. Therefore, this study was designed to evaluate the effects of khat on the pharmacokinetics of CLOP in rats. In this study, rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Based on our findings, CYP inhibition by khat extracts could be caused by the many alkaloids present in khat as aforementioned, and could also be a combination of the major constituents in khat, namely cathinone and cathine, or with a mix of other constituents. A recent study using LC-MS/MS method to explore the effect of khat on pharmacokinetics of an antiplatelet drug, clopidogrel, in rats also substantiated our previous findings that herb-drug interactions should be taken into consideration during prescribing to ensure an optimal dosage of drugs such as clopidogrel [7] .…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…Based on our findings, CYP inhibition by khat extracts could be caused by the many alkaloids present in khat as aforementioned, and could also be a combination of the major constituents in khat, namely cathinone and cathine, or with a mix of other constituents. A recent study using LC-MS/MS method to explore the effect of khat on pharmacokinetics of an antiplatelet drug, clopidogrel, in rats also substantiated our previous findings that herb-drug interactions should be taken into consideration during prescribing to ensure an optimal dosage of drugs such as clopidogrel [7] .…”
Section: Introductionsupporting
confidence: 74%
“…mephedrone) accompanied with alcohol [49] and co-abuse of controlled drugs such as heroin, cocaine, cannabis, ketamine and MDMA are popular among users [26] . Moreover, the concurrent polysubstance use among khat chewers are alcohols, cigarettes [47] , cardiovascular drugs [7] , cannabis, and benzodiazepine tablets, just to name a few [46] . Khat chewing reduces the bioavailability of co-administered antibiotics and antimalarial drugs, counteract with antihypertensive, antiarrhythmic and local anaesthetics but enhanced the effects of monoamine oxidase inhibitors and amphetamine like drugs [1] .…”
Section: Discussionmentioning
confidence: 99%
“…35 An in vivo study using rats found that rats treated with both khat plus clopidogrel had significantly lower clopidogrel metabolite produced due to inhibition of CYP enzyme by khat. 36 These studies supported that khat inhibited CYP activities but did not make any investigations on the specific compounds in khat that contributed to the CYPs inhibition. Therefore, it is plain to see that ingredients other than cathinone such as cathine and norephedrine, for instance, could be involved in the CYP inhibitory effects of khat.…”
Section: Discussionmentioning
confidence: 93%
“…This finding suggested that constituents of khat attenuate the antiplatelet aggregating properties of aspi-rin, and thereby neutralize the beneficial actions of aspirin (Alkadi et al, 2008). Alhazmi et al, 2020, reported a significant influence of khat on the peak ratio of clopidogrel (CLOP) metabolite, which was found to be significantly decreased in comparison to CLOP alone, suggesting a significant decrease in the conversion of CLOP to its active metabolite due to the inhibition of CYP450 enzymes by khat. Therefore, there might be a need for dose adjustment for regular khat chewers using CLOP.…”
Section: Antimalarial Drugsmentioning
confidence: 99%